Students’ technology acceptance of computer-based applications for analyzing animal behavior in an out-of-school lab - Henrich, Marvin; Formella-Zimmermann, Sandra; Gübert, Jennifer; Dierkes, Paul W. (Frontiers in Education, 2023)
Behavioral biology is a field that students find fascinating. To get the most out of the various benefits of teaching it, a practical approach should be followed. One way to do this is to use video recordings of animals which are analyzed using various software. However, learners will only benefit from this approach if they choose to actually use the provided technology. Therefore, it is critical to survey learners’ acceptance towards the use of software in the field of behavioral biology. For this purpose, 171 students were questioned at an out-of-school student lab called “KILab.” By applying the Technology Acceptance Model (TAM), we investigated students’ acceptance of authentic behavior evaluation software and possible factors influencing it. In addition, potential effects of the student lab on attitudes toward artificial intelligence and technology affinity were examined. The results show a high technology acceptance toward the used software and a dependence of this on the factors technology affinity and acceptance toward artificial intelligence. Furthermore, the use of the software has a positive impact on the self-assessed technology affinity and attitude toward artificial intelligence.The study thus shows that the use of video recordings and software for behavior analysis is generally suitable for educational use and can be a possible extension of the practical implementation of behavioral science education.